Surgical management of hepatolithiasis: an institutional experience of a rare disease - Kokoroskos, Nikolaos; Alifieris, Konstantinos; Agorgianitis, Loukas; Zouglos, Sotirios; Delis, Spyridon (International Surgery Journal, 2021)
Hepatolithiasis remains as a rare condition in the majority of western world countries. Although genetic, dietary and environmental factors have been associated with the disease, the exact etiology of this entity remains elusive. Several approaches; surgical and non-invasive have been well described. However, surgery remains the standard of care for definitive treatment of the disease. We sought to present the recent experience of our clinic regarding the surgical management of hepatolithiasis in the backgound of a narrative literature review. All adult patients with hepatolithiasis admitted to our center during the period 2018 to 2020 were included in the study. Patients’ demographics, comorbidities and preoperative characteristics were collected by chart review. All patients underwent open left lateral hepatectomy. Three cases with hepatolithiasis were identified. All of them were male and had been suffering from recurrent pyogenic cholangitis. All patients remained asymptomatic and disease-free through the entire follow-up, except one case that was complicated with bile leakage during the immediate postoperative period. Hepatolithiasis is currently a rare condition in the western world. Surgery is safe and effective treatment approach for refractory cases and, provided that it is performed by experts in hepatobiliary surgery, it remains imperative for the definitive treatment of the disease.